Pemberdayaan Santri Dalam Pengembangan Ekonomi Kreatif â€œKimi Bagâ€ Di Pondok Pesantren Al Qohar Klaten - Wijaya, Ning Karna; Aini, Soraya (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2020)
The empowerment of santri is a positive effort in realizing the goals of Islamic boarding schools in equipping students with religious knowledge and general science. This study aims to describe and to analyze the empowerment of santri in the Al Qohar Islamic Boarding School Klaten trough the development of creative economic products â€œKimi Bagâ€ as an effort to strengthen the soul of santri entrepreneurship. Santri can improve creativity and innovative abilities in developing creative economic ventures. Education and training is carried out by involving santri especially in production activities. The development of â€œKimi Bagâ€ products which are able to penetrate foreign markets provide added value for the santri in building motivation and enthusiasm for santri entrepreneurship. This santri empowerment program is expected to be able to instill a spirit of entrepreneurship that is not only worldly profit oriented but also based on the ukhrowi value. Â Pemberdayaan santri merupakan upaya positif mewujudkan tujuan pondok pesantren membekali santri dengan ilmu keagamaan dan ilmu pengetahuan umum. Penelitian ini bertujuan mendeskripsikan dan menganalisis pemberdayaan santri di Pondok Pesantren Al Qohar Klaten melalui pengembangan usaha ekonomi kreatif â€œKimi Bagâ€ sebagai upaya menguatkan jiwa entrepreneurship santri. Santri dapat menyalurkan kemampuan kreasi dan inovasi dalam mengembangkan usaha ekonomi kreatif. Pendidikan dan pelatihan dilakukan dengan melibatkan santri terutama dalam kegiatan produksi. Perkembangan produk â€œKimi Bagâ€ yang mampu menembus pasar luar negeri memberi nilai tambah tersendiri bagi para santri dalam membangun motivasi dan semangat entrepreneurship santri. Program pemberdayaan santri ini diharapkan mampu menanamkan jiwa entrepreneurship yang tidak hanya berorientasi keuntungan duniawi saja namun juga dilandasi nilai-nilai ukhrowi.